FOXP3+ Atypical Cells in Poikilodermatous Mycosis Fungoides - Antonia Syrnioti; Aikaterini Patsatsi; Elisavet Georgiou; Chrysostomos Avgeros; Triantafyllia Koletsa (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)